DISEÑO MUESTRAL PARA EL ESTUDIO DEL NIVEL DE SATISFACCIÓN DE LOS USUARIOS DEL DEPARTAMENTO DE NEONATOLOGÍA DE INSTITUTO ESPECIALIZADO MATERNO PERINATAL - Solano Dávíla, Olga (2006)
In Solano's investigation and other [8] determined the most important factors that affect in the level af satisfactian of the users of the Specializing Mother Perinatal Institute (IEMP) using the factor analysis, for what was necessary to design the scheme of sampling. In this context the objective of the present work is present the methodology of the sampling design, the allowed the generation of the imformation later analyzed with factor analysis and that will appear in a later publication. We considered the stratified random sampling with probabilities proportional to size f6} and the following strata were established : Service of intensive care and intermediate, Service joint housing of teenagers mother, Service joint housing of not teenagers mother and Service oi external office. All 245 mothers participants in the study were selected oi each o] four services that gives the IEMP, [ollounnq the scheme oi stratified random sampling with probabilities proportional to size. Por the calculation of the sample size we consider a limit [or estimation error of 6,4 %, a confidence level of 95 % and the historical informaiiori provided by the lEMP.